On Rational -Valued Characters of Certain Types of Permutation Group - Kirdar, M.S (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Tow   results  are  proved.  The  first  gives necessary  and   ullicientconditions for a permutation group to have the prope1ty that each of its rational - valued character can be written as (integral) linear combination of characters induced from the principal characters of certain subgroup. The mher presents that this property is extendable to direct product of groups.Examples give.